Deep-seabed mining: an environmental concern and a holistic social environmental justice issue - Cassotta, Sandra; Goodsite, Michael (Frontiers in Ocean Sustainability, 2024)
This study provides an update on the current regulatory and institutional landscape of deep-seabed mining (DSM). This regime formation occurred at a unique historical moment characterised by noteworthy legal developments. This is primarily because it applies to an activity (exploitation) that has not yet commenced, but is anticipated to commence in the near future, contingent on the finalisation of the regulatory regime. The legal environmental framework of DSM presents numerous challenges and gaps, however, it also has potential significance, particularly in the context of the ongoing green energy transition. This study aims to examine the intricate interplay between law and technology, examining the ‘law in context’ within the broader context of justice and geopolitics and examines the environmental framework of the DSM industry and seeks to address the existing regulatory gaps. This underscores the importance of adopting a precautionary approach and advocates the meticulous determination of the appropriate type of precautionary approach to be employed in the future. By holistically scrutinising DSM environmental law and policy and using the EU and Arctic as geopolitical-legal case studies, this article underscores that DSM is an environmental concern and a social environmental justice issue.